Pengaruh Kualitas Produk Dan E-Wom Dengan Brand Image Sebagai Mediasi Terhadap Keputusan Pembelian Produk Smartphone Realme Di Kota Pontianak - Anandha Shafitry, Mayfhuzha; Octaviani, Dina (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2024)
The development of information technology, especially smartphones, encourages people to decide to buy smartphones. In line with increasing competition in market share in Indonesia. However, in reality the Realme company is only ranked fifth in market share in Indonesia. This research aims to test and analyze the influence of product quality and e-wom with brand image as mediation on purchasing decisions for Realme smartphone products. The independent variables of this research are product quality and e-wom. The mediating variable is brand image while the dependent variable is purchasing decisions. This research uses primary data by distributing questionnaires to Realme smartphone consumers in Pontianak City. The collected data was analyzed using the Structural Equation Modeling (SEM) method with the WarpPls 8.0 application. The research results show that there is a direct influence between product quality and brand image. There is a direct influence between e-wom on brand image. There is a direct influence between product quality on purchasing decisions. There is a direct influence between e-wom on purchasing decisions. There is no direct influence between brand image on purchasing decisions. There is no relationship between product quality and purchasing decisions mediated by brand image. There is no relationship between e-wom and purchasing decisions mediated by brand image.